2019
DOI: 10.1111/eth.12879
|View full text |Cite
|
Sign up to set email alerts
|

Does acoustically simulated predation risk affect settlement and reproduction of a migratory passerine?

Abstract: Nest predation is one of the most important drivers of avian life history evolution and population dynamics. Increasing evidence suggests that birds are able to assess nest predation risk and avoid settling in high‐risk areas to increase their reproductive performance. However, the cues used for settlement decisions are poorly known in most species. Population sizes of the migratory wood warbler Phylloscopus sibilatrix are characterized by strong annual fluctuations, which are negatively correlated with the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Rodents have been documented to predate and/or destroy nests of several bird species in general (Kirkpatrick & Conway, ; Walankiewicz, ) and have been suspected to be an important nest predator of wood warbler nests via circumstantial indirect evidence (Mildenberger, ; Wesołowski, ; Wesołowski et al, ). However, direct evidence from using nest cameras in Northern Switzerland (this study, Grendelmeier et al, ), Marburg, Germany (Stelbrink, ), Wales, UK (Mallord et al, ), England, UK (Bellamy et al, ; Maziarz et al, ) and Białowieża National Park, Poland (Maziarz et al, ) now suggest that rodents are not important predators of wood warbler nests. Low predation by rodents is astonishing, considering that rodents were filmed moving around and even inspecting nests without predation occurring on many occasions (Maziarz et al, ).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Rodents have been documented to predate and/or destroy nests of several bird species in general (Kirkpatrick & Conway, ; Walankiewicz, ) and have been suspected to be an important nest predator of wood warbler nests via circumstantial indirect evidence (Mildenberger, ; Wesołowski, ; Wesołowski et al, ). However, direct evidence from using nest cameras in Northern Switzerland (this study, Grendelmeier et al, ), Marburg, Germany (Stelbrink, ), Wales, UK (Mallord et al, ), England, UK (Bellamy et al, ; Maziarz et al, ) and Białowieża National Park, Poland (Maziarz et al, ) now suggest that rodents are not important predators of wood warbler nests. Low predation by rodents is astonishing, considering that rodents were filmed moving around and even inspecting nests without predation occurring on many occasions (Maziarz et al, ).…”
Section: Discussionmentioning
confidence: 58%
“…(b) Rodent‐hunting predators (RHP hereafter) comprised the pine marten ( Martes martes ), the red fox ( Vulpes vulpes ), the stone marten ( Martes foina ), and the tawny owl ( Strix aluco ). We did not count house cats ( Felis catus ) as RHP, because we assume that their distribution and hunting behavior are strongly influenced by humans, and because they are not important nest predators in Switzerland (this study; Grendelmeier et al, ), in Germany (Stelbrink, ), in Wales and England (Bellamy et al, ; Mallord et al, ; Maziarz, Piggott, & Burgess, ) or in Poland (Maziarz et al, ). During 4 years, only four Eurasian lynx ( Lynx lynx ) and two European wildcats ( Felis silvestris silvestris ) could be photographed, but neither species depredated nests.…”
Section: Methodsmentioning
confidence: 99%
“…it is prioritized to the point of blind copying). Previous experiments (Grendelmeier et al, 2017 ; Stelbrink et al, 2019 ) found Wood Warblers did not respond to noise control playbacks of Common Wood Pigeon ( Columba palumbus ), demonstrating that attraction to conspecific playback is not attributable merely to the presence of novel, digital sounds.…”
Section: Methodsmentioning
confidence: 93%
“…In Jura (2013, 2014, 2017 and 2018), 43 nests were exposed to playback of conspecific songs to test if a simulated increase in density affected reproduction. Neither predator nor conspecific treatments affected the reproductive performance of wood warblers (Grendelmeier et al 2017, Stelbrink et al 2019, Riess 2021), and so we considered them valid for inclusion in the current study.…”
Section: Methodsmentioning
confidence: 99%